Causes of the Differences among Islamic Jurists Regarding the Principles of Usul al-Fiqh - Idris Salih Ahmad (Educational Foundation for Qur'anic Exegesis and Hadith Studies (Yayasan Pendidikan Tafsir Hadis), 2026)
Purpose – Juristic disagreement (ikhtilāf) has long been recognized as an inherent characteristic of Islamic jurisprudence (fiqh), reflecting the diversity of scholarly reasoning rather than doctrinal division. This study examines the principal causes of juristic disagreement among classical Muslim scholars and analyzes its epistemological significance for the development and adaptability of Islamic law. Design/methodology/approach – This study employs a qualitative library-based research design using descriptive and analytical methods. Primary and secondary sources in Islamic jurisprudence, uṣūl al-fiqh, and classical legal literature are critically examined to identify the methodological, linguistic, textual, and contextual factors underlying juristic disagreement. A thematic analysis is applied to synthesize recurring patterns across the scholarly tradition. Findings – The study demonstrates that juristic disagreement arises from multiple interconnected factors. These include differences in the authentication and interpretation of Qur’anic and Prophetic texts, linguistic variations within the Arabic language, divergent applications and prioritizations of uṣūl al-fiqh principles, and the influence of local customs (ʿurf) and changing social contexts. Variations in jurists’ intellectual backgrounds, reasoning methods, and access to legal evidence further contribute to differing legal conclusions. Rather than indicating inconsistency, these differences constitute a legitimate and productive feature of Islamic legal methodology that enables Sharīʿah to respond to diverse circumstances across time and place. Research implications/limitations – This study is conceptual and based exclusively on classical juristic literature. It does not investigate the contemporary application of ikhtilāf in modern legal systems. Future research may explore how classical theories of juristic disagreement inform contemporary ijtihād, legal reform, and comparative Islamic jurisprudence. Originality/value – This study contributes to Islamic legal scholarship by synthesizing the principal epistemological foundations of ikhtilāf into an integrated analytical framework. It highlights juristic disagreement as a source of methodological richness, legal flexibility, and intellectual dynamism, thereby reinforcing its enduring significance in the development of Islamic jurisprudence.